Immunometabolic regulation of vascular redox state: the role of adipose tissue - Oikonomou, E; Antoniades, C (Mary Ann Liebert, 2017)
SIGNIFICANCE: Vascular oxidative stress plays a crucial role in atherogenesis and cardiovascular disease (CVD). Recent evidence suggests that vascular redox state is under the control of complex pathophysiological mechanisms, ranging from inflammation to obesity and insulin resistance (IR). Recent advances: Adipose tissue (AT) is now recognized as a dynamic endocrine and paracrine organ that secretes several bioactive molecules, called adipokines. AT has recently been shown to regulate vascular redox state in both an endocrine and a paracrine manner through the secretion of adipokines, therefore providing a mechanistic link for the association between obesity, IR, inflammation and vascular disease. Importantly, AT behaves as a sensor of cardiovascular oxidative stress, modifying its secretory profile in response to cardiovascular oxidative injury. CRITICAL ISSUES: The present article presents an up-to-date review of the association between AT and vascular oxidative stress. We focus on the effects of individual adipokines on modulating reactive oxygen species production and scavenging in the vascular wall. In addition, we highlight how inflammation, obesity and IR alter the biology and secretome of AT leading to a more pro-oxidant phenotype with a particular focus on the local regulatory mechanisms of perivascular AT driven by vascular oxidation. FUTURE DIRECTIONS: The complex and dynamic biology of AT as well as its importance in the regulation of vascular redox state provide numerous opportunities for the development of novel, targeted treatments in the management of cardiovascular disease. Therapeutic modulation of AT biology could improve vascular redox state affecting vascular disease pathogenesis.